Impulsiveness, personality traits and executive functioning in patients with juvenile myoclonic epilepsy. (November 2020) - Gama, André Peres; Taura, Mariângela; Alonso, Neide Barreira; Sousa, Artur Menezes; Noffs, Maria Helena da Silva; Yacubian, Elza Márcia; Guilhoto, Laura Maria
Highlights: Patients with JME had higher levels of Motor and Total Impulsiveness compared to healthy controls. Motor Impulsiveness was associated with a higher rate of mild psychiatric disorders and worse myoclonic seizures control. Impulsiveness, personality traits and executive dysfunction were interrelated in patients with JME. Abstract: Purpose: To evaluate impulsiveness in adult patients with JME and its relationship with personality traits and executive functioning. Methods: Patients completed psychiatric evaluation (DSM IV), Barratt Impulsiveness Scale (BIS-11), Neo Revised Personality Inventory (NEO PI-R) and executive functioning evaluation comprising Controlled Oral Word Association (COWA), Digit Span, Trail Making Tests (TMT), Stroop Test (ST) and Wisconsin Card Sorting Test (WSCT). Healthy controls (63 % female, mean age 35.7 yrs. (±8.37)) were examined to allow calculation of z-scores. Results: 50 patients (70 % female; mean age 32.5 yrs. (±9.2)) presented higher scores of Total (z=-0.37; p = 0.005) and Motor Impulsiveness (z=-0.79; p < 0.001) on BIS-11. Motor Impulsiveness was associated with higher rates of mild psychiatric disorders (depression and anxiety) (p = 0.035) and worse myoclonic seizure control (p = 0.007). NEO PI-R showed differences on Neuroticism (z=-0.60; p < 0.001), Openness (z = 0.38; p = 0.043), Agreeableness (z=-0.38; p = 0.033) and Conscientiousness (z=-0.53; p = 0.003). There were positive correlations between BIS-11 and Neuroticism with Total, Motor and Non-Planning Impulsiveness, on the other hand, Conscientiousness was negatively correlated with these as well as with Attentive Impulsiveness. Patients performance was worse than that of controls on COWA (z=-0.43; p = 0.009) and WCST's Total Number of Completed Categories (z=-2.08; p = 0.005), Trials Taken to Complete First Category (z=-1.56; p = 0.013), Percentage of Total Errors (z=-1.56; p < 0.001), Perseverative Errors (z=-0.73; p = 0.002), Non-Perseverative Errors (z=-1.05; p = 0.003) and Conceptual Level Responses (z=-1.52; p < 0.001). Non-Planning Impulsiveness correlated with Performance (ST and TMT). Conclusion: Patients with JME present with impulsive behavior, personality features and executive dysfunction which are linked and may lead to lack of commitment in treatment and affect other aspects of life.